Relationship between Aortic Compliance and Impact of Cerebral Blood Flow Fluctuation to Dynamic Orthostatic Challenge in Endurance Athletes - Tomoto, Tsubasa; Imai, Tomoko; Ogoh, Shigehiko; Maeda, Seiji; Sugawara, Jun (Frontiers in Physiology, 2018)
Aorta effectively buffers cardiac pulsatile fluctuation generated from the left ventricular (LV) which could be a mechanical force to high blood flow and low-resistance end-organs such as the brain. A dynamic orthostatic challenge may evoke substantial cardiac pulsatile fluctuation via the transient increases in venous return and stroke volume (SV). Particularly, this response may be greater in endurance-trained athletes (ET) who exhibit left ventricular eccentric remodeling. The aim of this study was to determine the contribution of aortic compliance to the response of cerebral blood flow fluctuation to dynamic orthostatic challenge in ET and age-matched sedentary (SED) young healthy men. ET (n=10) and SED (n=10) underwent lower body negative pressure (LBNP) (-30mmHg for 4 minutes) stimulation and release the pressure that initiates a rapid regain of limited venous return and consequent increase in SV. The recovery responses of central and middle cerebral arterial (MCA) hemodynamics from the release of LBNP (~15seconds) were evaluated. SV (via Modeflow method) and pulsatile and systolic MCA (via transcranial Doppler) normalized by mean MCA velocity (MCAv) significantly increased after the cessation of LBNP in both groups. ET exhibited the higher ratio of SV to aortic pulse pressure (SV/AoPP), an index of aortic compliance, at the baseline compared with SED (P<0.01). Following the LBNP release, SV was significantly increased in SED by 14±7% (mean±SD) and more in ET by 30±15%; nevertheless, normalized pulsatile, systolic, and diastolic MCAv remained constant in both groups. These results might be attributed to the concomitant with the increase in aortic compliance assessed by SV/AoPP. Importantly, the increase in SV/AoPP following the LBNP release was greater in ET than in SED (P<0.01), and significantly correlated with the baseline SV/AoPP (r=0.636, P<0.01). These results suggest that the aortic compliance in the endurance athletes is able to accommodate the additional SV and buffer the potential increase in pulsatility at end-organs such as the brain.